2020
DOI: 10.15451/ec2020-08-9.32-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Highly cultural significant edible and toxic mushrooms among the Tseltal from the Highlands of Chiapas, Mexico

Abstract: The concept of cultural significance and its quantitative evaluation are useful to recognize which mushroom species (both edible and toxic) are the most relevant within a specific community. This work lists the most culturally significant edible and toxic species for the Tseltal groups in the Highlands of Chiapas. It also evaluates whether the composition and significance of these are dissimilar between the different Tseltal communities, proving the hypothesis that the edible and toxic species are not the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
2
6
0
1
Order By: Relevance
“…This concurs with studies on the Karbi people of Northeastern India, that found that some species lose their taste when ripened, and are therefore collected and consumed only at their juvenile stage [17]. This phenomenon has also been recorded in Southern Mexico, where the Tseltales report some edible species as toxic [13]. Similarly, the consumption of species known as toxic, such as Tricholoma equestre, has been documented [76].…”
Section: Traditional Knowledge Of Non-edible Mushroomssupporting
confidence: 87%
See 4 more Smart Citations
“…This concurs with studies on the Karbi people of Northeastern India, that found that some species lose their taste when ripened, and are therefore collected and consumed only at their juvenile stage [17]. This phenomenon has also been recorded in Southern Mexico, where the Tseltales report some edible species as toxic [13]. Similarly, the consumption of species known as toxic, such as Tricholoma equestre, has been documented [76].…”
Section: Traditional Knowledge Of Non-edible Mushroomssupporting
confidence: 87%
“…Our data showed that non-edible fungi species are key factors in the kosmos, corpus, and praxis of traditional knowledge of wild mushrooms [5]. We identi ed more than 100 non-edible taxa; in contrast, other ethnomycological studies usually mention up to 17 species that are recognized as toxic or poisonous [13,41]. Moreover, the characterization of local knowledge on non-edible mushrooms has been super cial and is generally the result generalizations from edible mushrooms [11,16,19,75].…”
Section: Traditional Knowledge Of Non-edible Mushroomsmentioning
confidence: 89%
See 3 more Smart Citations